A 3D kinematic analysis of breathing patterns in competitive swimmers - Silvatti, A. P.; Sarro, K. J.; Cerveri, P.; Baroni, G.; Barros, R. M. L. (Journal of Sports Sciences, 2012)
The purpose of this paper was to understand which differences long-term swimming training can cause on trunk mechanics during breathing and how these differences are related to the years of swimming training. The variations and coordination among trunk compartments were considered as target movement patterns. Video-based plethysmography was utilised for data acquisition and pre-processing. A group of swimmers, who followed a long-term intensive swimming training previously to this study, was compared with a non-swimmer control group. The participants of both groups performed quiet breathing and vital capacity tests. From the compartmental volumes associated with each breathing curves, the relative amplitude and cross-correlation among these volumetric time-varying signals were calculated, in order to analyse the relative partial volume variation and the coordination among trunk compartments involved in respiration. The results of a Mixed-ANOVA test (P = 0.05) revealed higher coefficient of variation (P < 0.001) and correlations among trunk compartments in the swimmers group when vital capacity was performed. Significant linear regression was found between the years of swim training and the coefficients of variation and correlation. The results suggest that after long periods of intensive swim training, athletes might develop specific breathing patterns featuring higher volume variations in the abdominal region and more coordination among compartments involved in forced respiratory tasks such as vital capacity.